The State and The Conflict Between Religion and Politics - Muayad Barakat Hassan (QALAAI ZANIST JOURNAL, 2024)
In light of the constant struggle between spiritual and mental issues imposed by philosophy as it always seeks to reach man at the top of awareness, to know the world around him and to live safely in a world where justice and equality prevail, the obstacles that stand in the way of achieving these goals remain the major problem of philosophy that tries to find appropriate solutions To her, philosophy is trying to find solutions, although it raises problems with its many assumptions. Our research is an attempt to highlight the importance of the state as an organizational political entity, which seeks to regulate the lives of individuals and groups, and that religion is only a part of the organizations of this state, and that the stronger the state, the more secure it is and achieves justice and equality in it, as it is the basis of successful organization. Religion is important for organizing life, but it is related to aspects of faith and cannot solve all the problems facing society, especially in the presence of differences in opinions and beliefs, as well as due to different religions.